Drinking Mineral Water and Low-Intensity Electromagnetic Radiation Combinational Effect on Rat Testes in Metabolic Syndrome: а Randomized Controlled Study - Yury N. Korolev; Lyubov V. Mikhailik; ORCIDLyudmila A. Nikulina (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
INTRODUCTION. To correct disorders in the male reproductive system organs in the metabolic syndrome, it seems reasonable to use a combined effect of natural and artificial therapeutic physical factors - drinking mineral water and low-intensity electromagnetic interference of ultrahigh frequency - on an experimental model of this disease. These factors have antioxidant, cytoprotective and regenerative effects and can have a wide range of effects on various adaptation and protective regulatory mechanisms. AIM. To reveal the development of metabolic and structural adaptation-protective reactions in rat testes under the combined effect of drinking sulphate mineral water and low-intensity electromagnetic radiation microwave in experimental simulation of metabolic syndrome. MATERIAL AND METHODS. The experiments were performed on 26 nonlinear male rats weighing 180-200g. The metabolic syndrome model was reproduced for 60 days using a high-caloric diet. The rats were divided into 3 groups: 1st (experimental)-rats received drinking sulfate mineral water in combination with microwave electromagnetic radiation against the background of a high-calorie diet; 2nd (control) - rats received only a high-calorie diet; 3rd (intact) - rats without any influences. Research methods: biochemical, lightoptical, morphometric, electron microscopy. Significance of differences was assessed by Student's t-test. RESULTS AND DISCUSSION. It was found that the combinational effect of drinking sulfate mineral water and low-intensity electromagnetic radiation microwave contributed to the enhancement of a number of adaptive and protective reactions in the testes of rats against the background of a high-caloric diet. They were mainly manifested in the activation of antioxidant protection and protein synthesis, improvement of spermatogenic cells differentiation processes and increase in their number, enhancement of cellular and intracellular regeneration. CONCLUSION. The data obtained can be used in the development of new approaches to the methods of adaptation-protective and compensatory-restorative processes enhancement in the organs of the male reproductive system in metabolic syndrome.